2012
DOI: 10.1007/s11011-012-9299-5
|View full text |Cite
|
Sign up to set email alerts
|

Grey matter abnormalities in social anxiety disorder: a pilot study

Abstract: While a number of studies have explored the functional neuroanatomy of social anxiety disorder (SAD), data on grey matter integrity are lacking. We conducted structural MRI scans to examine the cortical thickness of grey matter in individuals with SAD. 13 unmedicated adult patients with a primary diagnosis of generalized social anxiety disorder and 13 demographically (age, gender and education) matched healthy controls underwent 3T structural magnetic resonance imaging. Cortical thickness and subcortical volum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
100
5
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(125 citation statements)
references
References 79 publications
19
100
5
1
Order By: Relevance
“…While Syal et al (2012) [8] found no volumetric differences in the amygdala and hippocampus of subjects with SAD and controls, Irle et al (2011) [6] reported precisely the opposite to our findings; that is, volume reductions in the amygdala and hippocampus of subjects with generalized SAD relative to controls, which led us to take a closer look at the processes of atrophy/hypertrophy of limbic structures possibly associated with anxiety.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…While Syal et al (2012) [8] found no volumetric differences in the amygdala and hippocampus of subjects with SAD and controls, Irle et al (2011) [6] reported precisely the opposite to our findings; that is, volume reductions in the amygdala and hippocampus of subjects with generalized SAD relative to controls, which led us to take a closer look at the processes of atrophy/hypertrophy of limbic structures possibly associated with anxiety.…”
Section: Discussioncontrasting
confidence: 82%
“…Recently, however, Irle et al (2010) [6] found decreased amygdalar and hippocampal volumes in men with generalized SAD relative to controls and Liao et al (2011) [7] reported reduced gray matter volumes in the right hippocampus and inferior temporal gyrus in SAD, which were associated with enhanced resting-state functional connectivity. Finally, in the last and most recent article describing structural changes associated with social anxiety, Syal et al (2012) [8] described cortical thickness reductions in areas surrounding the fusiform and post-central gyri and, specifically on the right hemisphere, in the frontal, temporal, parietal, and insular cortices. Their volumetric analyses, however, showed no differences between patients with SAD and healthy controls in respect to the volume of the amygdala and hippocampus.…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis showed reduced cortical thickness in the orbitofrontal cortex (OFC), ACC, insula and temporal lobes in MDD patients (Schmaal et al, 2016). There are few cortical thickness studies of SAD patients, and only three original studies have reported cortical thickening in the left insula, right ACC and right temporal pole and cortical thinning in the right post-central cortex (Syal et al, 2012, Frick et al, 2013, Bruhl et al, 2014). However, the results of these studies may be confounded by the presence of medication and comorbid depression and anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have already shown that abnormal cortical thickness is present in both neurodegenerative disorders, such as Alzheimer’s disease, and acute or chronic pain disorders such as migraine [2729]. Interestingly, the pattern of modifications obtained was reminiscent of what is found in anxiety [30], depression [31], or dependence [32]. In accordance to the pattern of relationships between brain and clinical variables established in the present study, multiple psychological states may contribute to the overuse of acute medications, including fear of headache, anticipatory anxiety, obsessional drug-taking behaviors, depression and, psychological drug dependence.…”
Section: Discussionmentioning
confidence: 93%